SYSTEM OF STATISTICAL INDICATORS EXPRESSING THE STANDARD OF LIVING AND EXPENSES OF THE POPULATION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
In my scientific study, statistical indicators that express the standard of living and expenses of the population and the total income of the population, their composition and growth rates, as well as differences in the cross-section of regions were analyzed. The article covers issues such as income from labor activity, property and transfers, the importance of small entrepreneurship. The results show that in the first half of 2024, the total income of the population is 399.2 trillion. the net growth rate was 108.6%. The article also discusses income inequality, inter-territorial differences, and ways to reduce them. In the summary part, recommendations are given to increase the income of the population, diversify their composition and reduce territorial differences.